Adiponectin in anorexia nervosa and its modifiers: A meta‐regression study. Issue 10 (11th June 2022) - Tural, Umit; Iosifescu, Dan V.
Abstract: Objective: Adiponectin, which is secreted from adipose tissue, is a protein hormone. Although a large body of studies have found that circulating adiponectin levels increase in anorexia nervosa (AN) and caloric restriction, the effect of subtypes of AN and modifiers of adiponectin in AN are not yet known. Methods: A systematic search of electronic databases was performed using the search terms "adiponectin, " "anorexia nervosa, " and "eating disorder" up to January 2021. All studies published in peer‐reviewed journals, which included cases and control groups, were selected. The main outcome was the pooled standardized mean difference (SMD) in adiponectin levels between cases and controls, using the random‐effects model. Modifiers of SMD were tested via meta‐regression. Heterogeneity and publication bias were evaluated. Results: Thirty‐four studies met all eligibility criteria. The total sample of AN participants (Hedges' g  = .765, p  < .0001), and specifically the binge‐eating/purging (Hedges' g  = 1.211, p  < .00001) and restrictive subtypes (Hedges' g  = .913, p  < .00001) of AN have increased adiponectin plasma levels compared with healthy controls. Meta‐regression determined that insulin, IGF‐1, BMI, triglyceride, resistin, glucose, IL‐6 levels are significant modifiers of adiponectin levels. Discussion: Compared with controls, adiponectin levels are higher in AN overall, and specifically in the binge‐eating/purging and the restrictive AN subtypes. Many of metabolic parameters of glucose metabolism and pro‐inflammatory molecules modify the relationship between AN and adiponectin levels. Adipose tissue is important to maintain metabolic stability. Public Significance: Anorexia nervosa is a psychiatric disorder associated with a severe decrease in body weight and multiple metabolic abnormalities, including an increase in the hormone adiponectin. In this paper, we used meta‐analysis, a powerful statistical method, to aggregate data from 34 rigorously selected research reports. This enabled us to understand the value of adiponectin to differentiate clinical subtypes of anorexia nervosa and the relations between adiponectin and other important metabolic parameters. Resumen: Objetivo: La adiponectina, que es secretada del tejido adiposo, es una hormona proteica. Aunque una gran cantidad de estudios han encontrado que los niveles circulantes de adiponectina aumentan en la anorexia nerviosa (AN) y la restricción calórica, el efecto de los subtipos de AN y los modificadores de la adiponectina en la AN aún no se conocen. Métodos: Se realizó una búsqueda sistemática en bases de datos electrónicas utilizando los términos de búsqueda "adiponectina", "anorexia nerviosa" y "trastorno de la conducta alimentaria" hasta enero de 2021. Se seleccionaron todos los estudios publicados en revistas revisadas por pares, que incluían casos y grupos de control. El resultado principal fue la diferencia de medias estandarizada (DME) agrupada en los niveles de adiponectina entre los casos y los controles, mediante el modelo de efectos aleatorios. Los modificadores de DME se probaron mediante metarregresión. Se evaluaron la heterogeneidad y el sesgo de publicación. Resultados: Treinta y cuatro estudios cumplieron todos los criterios de elegibilidad. La muestra total de sujetos con AN (g de Hedges = 0.765, p  < 0.0001), y específicamente los subtipos de atracones/purgaciones (g = 1, 211 de Hedges, p  < 0.00001) y restrictivos (g = 0.913, p  < 0.00001) de AN tienen incrementados los niveles plasmáticos de adiponectina en comparación con los controles sanos. La metarregresión determinó que los niveles de insulina, IGF‐1, IMC, triglicéridos, resistina, glucosa, IL‐6 son modificadores significativos de los niveles de adiponectina. Discusión: En comparación con los controles, los niveles de adiponectina son más altos en la AN en general, y específicamente en los subtipos de atracones/purgaciones y AN restrictiva. Muchos de los parámetros metabólicos del metabolismo de la glucosa y las moléculas proinflamatorias modifican la relación entre los niveles de AN y adiponectina. El tejido adiposo es importante para mantener la estabilidad metabólica.